2015
DOI: 10.1177/1532673x15574594
|View full text |Cite
|
Sign up to set email alerts
|

Divided Government and Delay in the Legislative Process

Abstract: Despite a robust history of studies examining legislative outputs, little is known about how divided government affects the policymaking process. This article examines these dynamics by analyzing the relationship between divided government and delay in the consideration of important legislation. We also introduce a more nuanced measure of divided government-the strength of the president's party in Congress-that measures both the presence and magnitude of inter-branch conflict. Using a Cox proportional hazards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
(42 reference statements)
2
20
0
Order By: Relevance
“…To avoid arbitrarily splitting the sample at some value of the divided U.S. 4 There is a plethora of alternative approaches. More sophisticated measures we experimented with include the measure of strength of the president's party suggested by Hughes and Carlson (2015), the ratio of the number of failed bills to the number of total bills and various measures of polarization and/or ideological distance based on Poole and Rosenthal's NOMINATE scores (see Poole and Rosenthal 1997). The results using these more complicated measures are similar but less clear, leading us to prefer the simplest option.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid arbitrarily splitting the sample at some value of the divided U.S. 4 There is a plethora of alternative approaches. More sophisticated measures we experimented with include the measure of strength of the president's party suggested by Hughes and Carlson (2015), the ratio of the number of failed bills to the number of total bills and various measures of polarization and/or ideological distance based on Poole and Rosenthal's NOMINATE scores (see Poole and Rosenthal 1997). The results using these more complicated measures are similar but less clear, leading us to prefer the simplest option.…”
Section: Methodsmentioning
confidence: 99%
“…28 Also on measurement, some scholars have looked at delay rather than the number of laws passed in congress. There is some recent compelling evidence that divided government causes delay in important legislation (Hughes and Carlson, 2015) and, more specifically, in the budget process at the state level in the US (Kirkland and Phillips, 2018). However, looking specifically at welfare reforms, Bernecker (2016) found that divided US state governments are more likely to implement reforms than unified governments.…”
Section: Divided Versus Unified Governments and The Capacity For Enacting Reformsmentioning
confidence: 99%
“…Similarly, there is a small literature on the amount of time it takes Congress to complete key actions. This work uses duration analysis to show that the presence of divided government slows down legislative tasks such as the confirmation of judges, ratification of treaties, and the adoption of important bills (Binder and Maltzmann 2002;Shipan and Shannon 2003;Woon and Anderson 2012;Peake, Krutz, and Hughes 2012;Hughes and Carlson 2015). Like the existing work on late budgets, however, these efforts do not address issues of causality.…”
Section: Late State Budgets As a Measure Of Legislative Performancementioning
confidence: 99%